This preview shows pages 1–2. Sign up to view the full content.
This preview has intentionally blurred sections. Sign up to view the full version.View Full Document
Unformatted text preview: original function. Recall L[f'] = s*L[f] - f(0) and L[f''] = s 2 L[f] - s*f(0)- f'(0) Step II Use solve to compute the solution of the algebraic equation. In order to create the algebraic equation, let the Laplace transform of x be denoted as X, and recall that x(0) =0, x'(0) = 1. That give us s 2 X -3sX+2X-1 = 0. We want to solve this in Matlab. solve('s^2*X -3*s*X+2*X-1 = 0','X') ans = 1/(s^2-3*s+2) Step III Use ilaplace to obtain the solution of the initial differential equation. ilaplace(1/(s^2-3*s+2)) ans = exp(2*t)-exp(t) Solve the following ODEs using the three-step method x'' = -4x'-8x - 10cos2t, x(0)=x'(0)=0 x'' = -x'+2x - 15e t sint, x(0)=x'(0)=0...
View Full Document
This note was uploaded on 10/16/2009 for the course EL el6303 taught by Professor Prof during the Spring '09 term at NYU Poly.
- Spring '09